Financial Stability of the Enterprise (Methods and Methodology for Analysis) - Ivanova, Rositsa (Research Papers, 2025)
The question of the enterprises’ financial stability is relevant at all phases and stages of its development. The objective of this publication is to substantiate and present methods for analysis of the enterprise’s financial stability. In order to achieve this objective, the following tasks have to be solved: 1) to describe the nature of the enterprise’s financial stability; 2) to substantiate and systemize the absolute and relative indicators for the financial stability analysis; 3) to systemize the absolute and relative criteria that determine the relevant financial stability degrees. The object of this article refers to the financial stability of the enterprises, and its subject covers the methodological issues of the analysis of these enterprises’ financial stability.
Keywords: Financial stability; Enterprise; Criteria; Analysis; Methodology; Indicators